Optimization of Propane Dehydrogenation Process Conditions over Pt⁃Based Catalyst Based on Response Surface Methodology - Xilin PIAO; Hai WAN; Haotian CHI; Haijuan ZHANG (Shiyou huagong gaodeng xuexiao xuebao)
The propane dehydrogenation reaction is thermodynamically unfavorable, tnecessitating kinetic control through optimized process conditions. Single⁃factor experiments and multi⁃factor Response Surface Methodology (RSM) were employed to analyze and optimize propane dehydrogenation conditions over a PtSnK/Al₂O₃ catalyst, followed by experimental verification. First, single⁃factor experiments determined the range of values for the factors to be studied in the response surface methodology. Then, a Box⁃Behnken design with three factors (reaction temperature, space velocity, and hydrogen⁃hydrocarbon ratio) was used to optimize the reaction conditions of propane dehydrogenation by multifactor response surface methodology with propylene selectivity as the response value, and finally, the optimized process conditions were experimentally verified. Results indicated that the optimal reaction temperature, VHSV, and H₂/C₃H₈ molar ratio were 605 ℃, 2 200 h⁻¹, and 0.6, respectively. The theoretical propylene selectivity prediction under these conditions was 93.01%. The order of influence weight from largest to smallest was reaction temperature > H₂/C₃H₈ molar ratio > VHSV. Experimental verification yielded a propylene selectivity of 93.00% and propane conversion of 32.00%. Experimental determination of propylene selectivity is consistent with RSM predictions, confirming the model's reliability and credibility.